INTERNET FINANCIAL REPORTING: STUDI KOMPARASI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA DAN BURSA EFEK MALAYSIA - Emma Handayani; Luciana Spica Almilia (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2013)
Purpose of this research to know the difference quality internet financial reporting of manufacturing companies listed in Indonesia and Malaysia stock exchange. Sample for this research is website of manufacturing company are listed onIndonesia and Malaysia stock exchange. The research methods was using index internet financial reporting. The methods of data analysis was using descriptive analysis and mann whitney test. One of the survey findings was that listedmanufacturing companies in Indonesia stock exchange have a greater index internet financial reporting than Malaysia. Another major finding was that listed manufacturing companies in Indonesia and Malaysia stock exchange have a sameindex of content and technology. Another major finding was that listed manufacturing companies in Indonesia and Malaysia stock exchange have a difference index of timeliness and user support.Keyword : internet financial reporting, Malaysia, Indonesia, content, timeliness, technology, user support.